Climate Change Impacts and Solutions: An Environmental Sociological Perspective - Almutahar, Hasan; Sugino; Asmadi; Martinus; Apriyanto, Dhidik; Joko Triyono; Elyta, Elyta (Cita konsultindo, 2023)
The topic of climate change has evolved over time from being a global concern to a national strategic one. A nation should pay extra attention to the issue of climate change because it may affect its socio-environmental perspective. The third IPCC report states that climate change might intensify conflict or war; also, because it affects people's livelihoods, it can lessen the perspective of environmental sociology. This study, which employed a descriptive methodology, aims to clarify the problem of climate change and its relationship to the sociological environmental perspective, as well as the effects of climate change from the perspective of environmental sociology and potential solutions. According to the findings of the study Climate Change Impacts and Solutions: An Environmental Sociological Perspective, security may be indirectly impacted by climate change because it may have an impact on human livelihoods. In this scenario, the setting that is transformed into a field or a place where people work won't fully generate natural products, which can result in poverty. even make poverty worse. The government of Indonesia is taking action to address climate issues in order to reduce the level of climate change and reduce emissions by developing a strategy for implementing the Trans-Agency Programme in the National Medium-Term Development Planning (RPJMN) 2015-2019 with the National Action Plan - Climate Change Adaptation (RAN-API). Climate change can also worsen political stability. The NAP covers 17 technical entities with a focus on the economy, finance, human resources, environment, specific fields, and the legal system.